Penerapan Problem Based Learning untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas 3 di SDN Kutorejo 1 Tuban - Dede Nuraida; Ulfa Rusdiana; Yasshinta Ika Pratiwi; Odilia Gista Eka Lumitasari; Putri Novita Ampolina (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to improve the mathematics achievement of third-grade elementary school students through the implementation of the Problem-Based Learning (PBL) model within the framework of Classroom Action Research (CAR). The research was conducted at UPT SD Negeri Kutorejo 1 Tuban and involved 27 students over two instructional meetings. The study was carried out in two cycles, each comprising the stages of planning, implementation, observation, and reflection. Data collection techniques included learning outcome tests, interviews, and documentation. The data were analyzed using both quantitative and qualitative descriptive approaches. The findings indicate a notable improvement in students’ average mathematics scores, increasing from 79.47 in the first cycle to 83.91 in the second cycle. This improvement reflects the positive impact of the PBL model on students' conceptual understanding, problem-solving abilities, and active participation during the learning process. Throughout the intervention, students demonstrated increased engagement in group discussions, greater confidence in expressing ideas, and enhanced independence in addressing given problems. The PBL model proved effective in fostering active, collaborative, and meaningful learning. By presenting real-world contextual problems, the model not only enhanced students’ academic performance but also promoted the development of critical thinking, communication, and social skills. These outcomes align with 21st-century educational goals, which emphasize the cultivation of higher-order thinking skills. Theoretically, this study reinforces the effectiveness of PBL as an innovative pedagogical approach for mathematics instruction at the elementary level. It is recommended that educators systematically and consistently implement the PBL model in classroom practice. Future research is encouraged to explore the interaction between individual student characteristics and instructional models, in order to further optimize learning outcomes across various subject areas.